Investigating Batak Toba Subject Properties: A Typological Analysis of Grammatical Relations and Behaviors - Nurianti Sitorus; Mulyadi (Universitas Islam Negeri Palopo, 2026)
This study investigates the subject properties of Batak Toba Language (BBT) from a typological perspective by examining grammatical relations through syntactic behavior. Batak Toba is typologically important because it represents an Austronesian language with flexible constituent order and dynamic grammatical alignment, contributing to broader discussions on subjecthood and alignment systems. Previous studies on BBT have mainly focused on pivot systems, verbal valency, and language variation, while subject properties remain underexplored. This study employed a qualitative descriptive method within a linguistic typology framework. The data consisted of 100 verbal clauses collected from published sources and native speakers, which were analyzed using six syntactic parameters proposed by Artawa (2018). The findings show that BBT exhibits flexible subject behavior in which grammatical relations are influenced by constituent order, discourse functions, and semantic roles. Fronting constructions allow non-subject constituents to occur in clause-initial position, while floating quantifiers affect semantic interpretation and coreference relations. Relativization patterns indicate that subjects are more accessible than other grammatical functions, and interrogative constructions emphasize focus marking and constituent prominence. Furthermore, BBT predominantly exhibits verb-initial patterns such as VS, VOS, and VSO, while also showing tendencies toward flexible nominative-accusative alignment with split-S characteristics in specific constructions. Overall, the study contributes to typological discussions on subjecthood, grammatical relations, and alignment systems in Austronesian languages.